2020
DOI: 10.1111/jvim.15749
|View full text |Cite
|
Sign up to set email alerts
|

Role of electrolyte abnormalities and unmeasured anions in the metabolic acid‐base abnormalities in dogs with parvoviral enteritis

Abstract: Background The strong ion model (SIM) is an alternative paradigm in the characterization of acid‐base disturbances particularly in complex disorders. Hypothesis/Objectives To compare the acid‐base changes in dogs with parvoviral enteritis (PE) using the Henderson‐Hasselbalch (HH) approach, with 2 strong ion approaches. Animals Forty‐four dogs with PE, and 16 age‐matched control dogs. Methods Prospective controlled observational study. Acid‐base status was evaluated using the HH model, Fencl‐Stewart (FS) approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…Of relevance is the finding that the simplified strong-ion acid-base abnormalities had a higher sensitivity in detecting an acid-base disorder and therefore more explanatory power than the traditional Henderson-Hasselbalch approach which is in line to numerous previous investigations. [9][10][11]15,20 Stepwise linear regression analysis indicated that plasma L-lactate concentration was the most important predictor of venous blood pH. This was an expected finding based on the high prevalence of hyper-L-lactatemia in this study sample 4,12 that was most likely caused by inadequate oxygen delivery to ischemic gastrointestinal tissues secondary to volvulus, torsion, or luminal distention.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Of relevance is the finding that the simplified strong-ion acid-base abnormalities had a higher sensitivity in detecting an acid-base disorder and therefore more explanatory power than the traditional Henderson-Hasselbalch approach which is in line to numerous previous investigations. [9][10][11]15,20 Stepwise linear regression analysis indicated that plasma L-lactate concentration was the most important predictor of venous blood pH. This was an expected finding based on the high prevalence of hyper-L-lactatemia in this study sample 4,12 that was most likely caused by inadequate oxygen delivery to ischemic gastrointestinal tissues secondary to volvulus, torsion, or luminal distention.…”
Section: Discussionsupporting
confidence: 56%
“…Of relevance is the finding that the simplified strong‐ion acid‐base abnormalities had a higher sensitivity in detecting an acid‐base disorder and therefore more explanatory power than the traditional Henderson‐Hasselbalch approach which is in line to numerous previous investigations. 9 , 10 , 11 , 15 , 20 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Venous blood gas revealed metabolic acidosis in eight dogs (89%), with a decrease in electrolytes. Metabolic acidosis, hypokalemia, hyponatremia, and hypochloremia are common findings in dogs with CPE resulting from vomiting and diarrhea [ 44 , 45 , 46 ]. Three dogs presented lactic acidosis, which is consistent with the results of a recent study [ 47 ].…”
Section: Discussionmentioning
confidence: 99%